Boredom, Shanzhai, and Digitisation in the Time of Creative China - de Kloet, Jeroen; Fai Chow, Yiu; Scheen, Lena (Asian Visual Cultures, 2019)
With its emergence as a global power, China aspires to transform from Ÿmade in ChinaŒ to Ÿcreated in ChinaŒ. Mobilised as a crucial source for solid growth and Ÿsoft power,Œ creativity has become part of the new China Dream. Boredom, Shanzhai, and Digitisation in the Time of Creative China engages with the imperative of creativity by aligning it to three interrelated phenomena: boredom, shanzhai, and digitisation. How does creativity help mitigate boredom? Does boredom incubate creativity? How do shanzhai practices and the omnipresence of fake goods challenge notions of the original and the authentic? Which spaces for expressions and contestations has China's fast-developing digital world of Weixin, Taobao, Youku, and Internet Plus Policy opened up? Are new technologies serving old interests? Essays, dialogues, audio-visual documents, and field notes, from thinkers, researchers, practitioners, and policy-makers, examine what is going on in China now, ultimately to tease out its implication to our understanding of ŸcreativityŒ.